Prognostic factors in alveolar soft part sarcoma: A SEER analysis. Issue 5 (25th January 2016) - Wang, Haotong; Jacobson, Alex; Harmon, David C.; Choy, Edwin; Hornicek, Francis J.; Raskin, Kevin A.; Chebib, Ivan A.; DeLaney, Thomas F.; Chen, Yen‐Lin E.
Abstract : Objectives: We reviewed the clinical characteristics and outcomes of patients treated for alveolar soft part sarcoma (ASPS) and analyzed the effect of surgery for patients presenting with and without metastatic disease (DM). Methods: The SEER Registry was queried for patients with ASPS from 1973–2012. The Kaplan–Meier estimate and Cox proportional hazards were used to analyze survival outcomes and risk variables. Results: Among 251 patients, 43% had DM and 67% locoregional disease (LR) on presentation. The 5‐year overall survival (OS) for all patients was 56% (82% and 27% for LR and DM, respectively). Multivariate analysis identified older age (hazard ratio [HR] = 1.03 per year, P < 0.001), tumor size >10 cm (HR = 2.76, P = 0.013), DM at diagnosis (HR = 3.79, P < 0.001), and truncal primary site (HR = 1.63, P = 0.035) as independent factors predicting worse OS. For LR patients, surgery plus radiotherapy (RT) resulted in better OS compared to surgery alone P = 0.014. For DM patients, primary site surgery significantly improved survival ( P < 0.001). Conclusion: ASPS presents with high metastasis rate but has a relatively indolent clinical course and a favorable prognosis with prolonged survival. Aggressive treatment using adjuvant RT with surgery is indicated in patients with LR disease and surgery is indicated in patients presenting with DM. J. Surg. Oncol. 2016;113:581–586 . © 2016 Wiley Periodicals, Inc.